Shamkir: History of the City in R. Mehdixanov’s Works - Y. P. Ivanova (Научный диалог, 2019)
The researches of the Azerbaijani historian Rəsul Mehdixanov are discussed, which are dedicated to the history of the city of Shamkir, including a monograph published in 2016 and certain articles of the author, devoted, in particular, to the German colony existing in Shamkir in the 19th century. It is shown that the studies by R. Mehdixanov provide the data on the development of one of the ancient cities in northwestern Azerbaijan. In particular, it is reported that the book “The History of the City of Shamkir” analyzes information about the origin of the city, the geography of the Shamkir region and Shamkir history from ancient times to the early 20th century, and the articles explore certain aspects of the history of the city, especially after its inclusion in the Russian Empire. It is noted that a significant part of R. Mehdixanov’s research on the history of the city of Shamkir was made up of works devoted to the German settlement Annenfeld, which existed on the site of ancient Shamkir in 1818-1924 and became the basis for the modern city of Shamkir. The article identified several discrepancies and gaps concerning the history of the city of Shamkir and unaffected in the writings by R. Mehdixanov.